High inclusion of corn gluten meal supplemented with butyric acid; Impacts on growth, immunology, histopathology, and metabolomics of pacific shrimp - Mpwaga Alatwinusa Yohana; Gyan Watson Ray; Kou Shiyu; Beiping Tan; Qihui Yang (Aquaculture Reports)
This research aimed to examine the impacts of adding butyric acid (BA) at elevated levels to corn gluten meal (CGM) in the Pacific shrimp diet. This study analyzed how adding BA to the diet impacts shrimp growth performance, immunology, metabolomics, and histopathological responses. A total of 720 shrimp were divided into six groups, each receiving a different level of BA supplementation: 0 %, 0.5 %, 1 %, 1.5 %, 2 %, and 2.5 %. The experiment spanned 56 days, with three replicates for each group. The initial mean weight of the shrimp was 0.18 ± 0.00 g. The results of the study indicated that final weight (FW), weight gain rate (WGR), and specific growth rate (SGR) all showed significant increases with increased levels of dietary BA (P < 0.05). The survival rate (SR) was 100 % across all treatment groups. Additionally, dietary BA led to a significant decrease in feed conversion ratio (FCR), with the most pronounced effect observed in the 1.5 % BA group (P < 0.05). The addition of BA to the diet resulted in a significant increase in the activities of alkaline phosphatase (AKP) and acid phosphatase (ACP). At the same time, the levels of aspartate and alanine aminotransferase decreased significantly (P < 0.05). Interestingly, malondialdehyde (MDA) levels decreased with higher BA supplementation, but superoxide dismutase (SOD) activity increased in shrimp-fed BA diets. Histological analysis of the hepatopancreas showed that shrimp-fed diets containing 1 % and 1.5 % BA had significantly higher B and R-cell numbers than the control group. Metabolomics analysis revealed that fatty acids such as palmitic acid, docosahexaenoic acid (DHA), stearic acid, and arachidonic acid were up-regulated in BA diets. The slope broken-line regression analysis of WGR against dietary BA levels suggested that the optimal BA requirement for L. vannamei shrimp was estimated to be 1.25 %.